2018
DOI: 10.1596/978-1-4648-1238-5
|View full text |Cite
|
Sign up to set email alerts
|

Toward Great Dhaka: A New Urban Development Paradigm Eastward

Abstract: This work is a product of the staff of The World Bank with external contributions. The findings, interpretations, and conclusions expressed in this work do not necessarily reflect the views of The World Bank, its Board of Executive Directors, or the governments they represent. The World Bank does not guarantee the accuracy of the data included in this work. The boundaries, colors, denominations, and other information shown on any map in this work do not imply any judgment on the part of The World Bank concerni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 39 publications
0
20
0
Order By: Relevance
“…Instead, when it comes to urban agglomerations, studies suggest establishing functional land markets, improving land use, providing urban transport and other basic public services, and fostering housing finance markets. These are the key components of policies for addressing the urban order in cities (Bird et al 2018;Brueckner and Lall 2015;Duranton and Venables 2018;Ellis and Roberts 2015;.…”
Section: B2b Spilloversmentioning
confidence: 99%
“…Instead, when it comes to urban agglomerations, studies suggest establishing functional land markets, improving land use, providing urban transport and other basic public services, and fostering housing finance markets. These are the key components of policies for addressing the urban order in cities (Bird et al 2018;Brueckner and Lall 2015;Duranton and Venables 2018;Ellis and Roberts 2015;.…”
Section: B2b Spilloversmentioning
confidence: 99%
“…Bangladesh has become one of the most densely populated countries in the world, with an area of 147,570 km 2 and a population of 149,772,364. Dhaka, the capital of Bangladesh, a fast-growing megacity of South Asia, had a population of 2.2 million in 1975, which has increased to 18 million in 2017, with a growth rate of 4.56% annually [26]. Data from the "Household Income and Expenditure Survey 2016" [27] revealed that about 28% of the population was considered extremely poor (urban: 7%; rural: 21%, individually).…”
Section: Energy and Power Sectormentioning
confidence: 99%
“…With rapid urbanisation in LMICs [3], the neighbourhoods where many children now grow up are fundamentally different from the rural communities of previous generations. Nowhere is this clearer than in Dhaka, Bangladesh, where the city population grows by 3 to 4% every year and as of 2019, an estimated 18 million live within the greater Dhaka area [4].…”
Section: Introductionmentioning
confidence: 99%